Automotive heating and air conditioning - Schnubel, Mark (Today's technician, 2005)
Key updates in the areas of electronic systems, climate control, and case and duct systems are just some of the enhancements to the newly revised Today's Technician: Automotive Heating and Air Conditioning, Third Edition. This two-book set continues to provide users with a complete introduction to automotive heating and air conditioning. In addition, a new chapter on both retrofits and future trends points to the prospect of R-744 becoming the next preferred automotive refrigerant. Also included is a comparison of components used in R-134A systems with those used in R-12 systems and a discussion of the various refrigerants approved to replace R-12. Coverage of modern engine cooling and heating systems incorporates discussion of the requirements for a closed cooling system and the operation of various types of cooling fans. Finally, all job sheets in the Shop Manual now include the exact NATEF and ASE tasks that each job sheet correlates to, ensuring that readers are well prepared for employment in the automotive trade.